2005
DOI: 10.1111/j.1600-0838.2004.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of delayed‐onset muscle soreness on stretch reflexes in human low back muscles

Abstract: The aim of the study was to investigate the effect of moderate delayed-onset muscle soreness (DOMS) on the short latency stretch reflex (SLR) and long latency stretch reflex (LLR) response i.e. electromyographic (EMG) onset latencies and EMG amplitudes in erector spinae (ES). Nine males with muscle soreness (DOMS group) were tested 24, 48 h, and 7 days post-exercise. Eight males (control group) were tested likewise. EMG was measured from ES bilaterally at the level of L3/L4. The SLR was elicited by mechanicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
2
14
1
Order By: Relevance
“…Another limitation of this review is the limited number of studies investigating muscle fatigue, spinal tissue creep, and musculoskeletal pain effects. Diverse sensorimotor and biomechanical external perturbation, such as vibration (Arashanapalli and Wilson, 2008; Santos et al, 2008; Arora and Grenier, 2013; MacIntyre and Cort, 2014) and delayed onset muscle soreness (Hjortskov et al, 2005), were identified during the preliminary search. However, an insufficient number of studies was available to consider these topics in the review.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this review is the limited number of studies investigating muscle fatigue, spinal tissue creep, and musculoskeletal pain effects. Diverse sensorimotor and biomechanical external perturbation, such as vibration (Arashanapalli and Wilson, 2008; Santos et al, 2008; Arora and Grenier, 2013; MacIntyre and Cort, 2014) and delayed onset muscle soreness (Hjortskov et al, 2005), were identified during the preliminary search. However, an insufficient number of studies was available to consider these topics in the review.…”
Section: Discussionmentioning
confidence: 99%
“…Another method for testsing muscle disorders is electromyography (EMG), which assess the muscle function by capturing electrical signs deriving from an active muscle 15 and evaluates different parameters, such as muscle relaxation 16,17 , muscle weakness 18,19 and activity of motor units 20,21 . Long-term surface EMG recordings have revealed large inter-individual variation in trapezius activation patterns related to individual variation in structural factors (e.g., anatomy, fiber composition), contrasted by intra-individual consistency in repeated recordings likely representing an expression of idiosyncratic muscle activation patterns, i.e., motor habits 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the excitability (amplitude) of the short-latency lumbar paraspinal stretch reflex (Dimitrijevic et al, 1980;Hjortskov et al, 2005;Zedka et al, 1999) (Kissling, R, Brunner C, Jacob HAC 1990 -cited in Herzog clinical biomechanics of Spinal manipulation p. 201), and to our knowledge no studies have examined the stability of this measurement. Our findings indicate that the short-latency stretch reflex amplitude exhibits high reliability-as evidenced by the CV and ICC data-although large between-subject differences in the absolute voltage values were observed.…”
Section: Discussionmentioning
confidence: 97%
“…More than 25-years ago it was noticed that deep somatic or visceral pain leads to local increases in muscle tone/spasm (Travell and Simons, 1983), and many authors have speculated that an increased stretch reflex gain underlies the increased muscle tone in painful muscles as is commonly observed in LBP (Johansson and Sojka, 1991;Knutson, 2000;Korr, 1975;Matre et al, 1998). However, the reflex activity of human paraspinal muscles has received little scientific attention (Fuhr and Smith, 1986;Hjortskov et al, 2005;Kugelberg and Hagbarth, 1958;Skotte et al, 2005;Tani et al, 1997;Zedka et al, 1999), and to our knowledge only a few studies have ever examined the amplitude (or excitability) of this reflex pathway in these muscles (Dimitrijevic et al, 1980;Hjortskov et al, 2005;Zedka et al, 1999). Consequently, the second purpose of this work was to use an electromechanical tapping system to measure the amplitude of the short-latency stretch reflex of the lumbar paraspinal muscles, and to examine the test-retest reliability of this outcome.…”
Section: Introductionmentioning
confidence: 97%